2006
DOI: 10.18388/abp.2006_3302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the replicative age and cell volume in Saccharomyces cerevisiae.

Abstract: Reaching the limit of cell divisions, a phenomenon referred to as replicative aging, of the yeast Saccharomyces cerevisiae involves a progressive increase in the cell volume. However, the exact relationship between the number of cell divisions accomplished (replicative age), the potential for further divisions and yeast cell volume has not been investigated thoroughly. In this study an increase of the yeast cell volume was achieved by treatment with pheromone alpha for up to 18 h. Plotting the number of cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Scheme drawn on the basis of cell volumes measured experimentally (Zadrag-Tecza et al, 2009). increase in cell size does not necessarily lead to a shortening in life span'. However, the results of our studies brought quite different results, fully supporting the hypertrophy hypothesis (Zadrag et al, 2005(Zadrag et al, , 2006Zadrag-Tecza et al, 2009). Moreover, experimental elevation of cell volume by nocodazole treatment or by growing the cdc28 mutant at restrictive temperature (Yang et al, 2011) also shortened rls.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…Scheme drawn on the basis of cell volumes measured experimentally (Zadrag-Tecza et al, 2009). increase in cell size does not necessarily lead to a shortening in life span'. However, the results of our studies brought quite different results, fully supporting the hypertrophy hypothesis (Zadrag et al, 2005(Zadrag et al, , 2006Zadrag-Tecza et al, 2009). Moreover, experimental elevation of cell volume by nocodazole treatment or by growing the cdc28 mutant at restrictive temperature (Yang et al, 2011) also shortened rls.…”
Section: Resultssupporting
confidence: 52%
“…According to the rules of methodology of sciences, the natural phenomenon, which always accompanies the studied one, is most probably its causative factor if other accompanying phenomena can be eliminated without elimination of the phenomenon studied (Ducheyne, 2008). We have postulated Zadrag et al, 2006) that simply reaching excessive volume by yeast cells at the end of their reproductive period is responsible for their inability to undergo further reproduction. The only a priori assumption, on which all hypotheses are based, is that the level of any senescence factor cannot increase infinitely.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The key point in this debate centers around whether increased cell size and/or hypertrophy actually reduces RLS or is merely correlative with senescence in yeast. To date, four experiments favor a causative role for increased cell size and/or hypertrophy in senescence Zadrag et al, 2006;Zadrag-Tecza et al, 2008;Yang et al, 2011). First, although initial experiments with alpha factor demonstrated that RLS was not reduced despite increased size (Kennedy et al, 1994), follow-up experiments have concluded the opposite (Zadrag et al, 2006;Bilinski et al, 2012a, b).…”
mentioning
confidence: 99%